DINAMIKA KERUANGAN PESISIR KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Yakobus C. W. Siubelan; Kukuh Murtilaksono; Djuara P. Lubis (Graduate School Bogor Agricultural University (SPs IPB), 2015)
This research aims to 1) analyze the dynamics of land use change in the coastal area of Kupang and 2) study the relationship of land use change, population growth, and incremental of garbage (during 1999-2030), and 3) formulate policy of the development of coastal areas. Analysis of land use change using geographic information system (GIS) and analysis of dynamic systems were applied in this research. The result showed that there has been a significant land use change during periode of 1999 - 2013. Dryland farming/shrub drastically decreased and being converted into residential area of 836.53 ha changes.The land use simulation of 2030 shows that the residential area reached to 3.337.05 ha, more than the existing area as 3,163 .48 ha. The changes has highly related to population growth and garbage volume, therefore it needs strong comprehensive policy including tightening of development permission, development of vertical housing and increasing for garbage storage facility and its transporter. Keywords: land use change, coastal area of Kupang City, dynamic systems